Dynamic simulation and optimisation of tubular polymerisation reactors in gPROMS - Asteasuain, Mariano (2001)
In this paper a dynamic model of the high-pressure polymerisation of ethylene in tubular reactors is introduced and a dynamic optimisation problem is formulated for studying start-up strategies. The optimisation objectives proposed are to maximise outlet conversion and optimise the time necessary for it's stabilisation while keeping product molecular properties between commercial ranges. Results are shown giving the time responses for temperature, number-average molecular weight and conversion along the reactor axial distance, which were obtained using different control variable profiles. Improving in reactor productivity is achieved. The interface gOPT of the gPROMS simulator was used to resolve the optimisation problem and to perform the simulations.